PERFORMANCE EVALUATION OF PLASTIC GRANULES AND QUARRY DUST AS FINE AGGREGATE IN M40 GRADE CONCRETE - Nisha, Mrs.I.Rahmath; Ganga, Mrs.T. (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
In this context an experimental study is done based on Quarry Dust Wastes (QDW) and polypropylene plastic granules (PPG) for replacement of fine aggregate in concrete. The strength properties of M40 grade concrete is studied with different proportions of plastic granules and quarry dust along with addition of 1% super plasticizer. The various proportions of plastic and quarry dust used are 25% and 30% replacement by volume of river sand in the concrete. Strength tests are carried out with different proportions of replacements of river sand with QDW and PPG. Cube specimens, cylinder specimens and prism specimens of 9 numbers each were cast for different proportions of M40 concrete , cured and tested for 7 ,14 and 28 days. Compression, split tensile and flexural strength tests were done and the results are compared with 100% river sand concrete specimens. Keyword - river sand, polypropylene plastic granules, quarry dust, industrial wastes, super plasticizer.